The Gut-Immune-Brain Axis in Autism Spectrum Disorders; A Focus on Amino Acids - van Sadelhoff, Joris H. J.; Perez Pardo, Paula; Wu, Jiangbo; Garssen, Johan; van Bergenhenegouwen, Jeroen; Hogenkamp, Astrid; Hartog, Anita; Kraneveld, Aletta D. (Frontiers in Endocrinology, 2019)
Autism spectrum disorder (ASD) is a range of neurodevelopmental conditions that affect communication and social behavior. Besides social deficits, systemic inflammation, gastrointestinal immune-related problems and changes in the gut microbiota composition are characteristic for people with ASD. Animal models showed that these characteristics can induce ASD-associated behavior, suggesting an intimate relationship between the microbiota, gut, immune system and the brain in ASD. Multiple factors can contribute to the development of ASD, but mutations leading to enhanced activation of the mammalian target of rapamycin (mTOR) are reported frequently. Hyperactivation of mTOR leads to deficits in the communication between neurons in the brain and to immune impairments. Hence, mTOR might be a critical factor linking the gut-brain-immune axis in ASD. Pharmacological inhibition of mTOR is shown to improve ASD-associated behavior and immune functions, however, the clinical use is limited due to severe side reactions. Interestingly, studies have shown that mTOR activation can also be modified by nutritional stimuli, in particular by amino acids. Moreover, specific amino acids are demonstrated to inhibit inflammation, improve gut barrier function and to modify the microbiota composition. In this review we will discuss the gut-brain-immune axis in ASD and explore the potential of amino acids as a treatment option for ASD, either via modification of mTOR activity, the immune system or the gut microbiota composition.